PENGARUH KUALITAS PESAN, DAYA TARIK IKLAN DAN FREKUENSI PENAYANGAN TERHADAP EFEKTIVITAS IKLAN MEDIA TELEVISI PADA PRODUK SEPEDA MOTOR MEREK HONDA - SAMUEL T.U.A GINTING, (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2020)
The competition in the motorcycle industry led the Brand Sole Agent (ATPM) to develop a strategy so that its products could be accepted in the market, including television advertisements. Honda has spent a lot of money to make advertising has decreased market share from year to year. The problem faced is how to design ads that are unusual, creative and can attract the attention of the audience so that these ads can be effective. In this research, we will find out the effect of message quality, attractiveness of advertisements and frequency of views on the effectiveness of television media advertisements on Honda brand motorcycle products (studies on Honda motorcycle product advertisements). This study uses multiple linear regression analysis with SPSS Version 24.0. The population used is the Medan City Society with the criteria are Honda motorcycle users and have seen Honda ads. While the samples used were 100 people with accidental sampling method. The results showed that the message quality, ad appeal, and frequency of views had a positive and significant effect on the effectiveness of advertisements either partially or simultaneously. As such, Honda must pay attention to these three things to produce effective advertising so that the huge costs that have been spent get the appropriate results.